Making social protection work for gender equality: What does it look like? How do we get there? - Shahrashoub Razavi; Ian Orton; Christina Behrendt; Lou Tessier; Veronika Wodsak; Krithi Dakshina Ramaswamy; Alix Machiels (International Labour Organization (ILO), 2024)
Attesting to feminist interest in social protection, there exists today a voluminous and growing literature, produced by academics, international organizations, civil society and think tanks, examining the gender content and impacts of social protection policies. The added value of this paper is that it is the first time that the ILO's Universal Social Protection Department has produced a consolidated message on its perspective and approach to enhancing the gender-responsiveness of social protection policies, anchored in international social security standards and guided by a life-cycle approach to system-building. In so doing, the paper underlines the critical interconnections and need for coherence between social protection policies and economic policies, especially employment policies (focusing on all types of employment), on one hand, and social protection policies and public investment and regulation of social services (especially healthcare and care services) on the other. It also both highlights new data and underlines remaining data gaps that need to be urgently closed to enable the monitoring of the impact of social protection policies on gender equality. It intends to encourage social protection policymakers, as well as social partners and other stakeholders, everywhere to think more systematically about the gender content and impact of social protection when they are advocating for or modifying existing policies, and designing and administering schemes, to better promote gender equality.
Keywords: 330